Evaluation of the Policy of the Amar Patria Unit 06 Joint Business Group (Kube) Program in Kerta Jaya Village, Padalarang District, West Bandung Regency - Muhammad Ridwan Silehu (Sean Institute, 2025)
The purpose of implementing the KUBE program is to improve the community's economy, through community empowerment programs, the program is not only focused on improving the economy, but more on improving the welfare of the community. The local government, West Bandung Regency through the Social Service plans and implements the program. To measure the success of the program, an evaluation is necessary. Policy evaluation is an activity to assess or see the success or failure of a program/policy carried out by an individual/organization. The research method used is descriptive analysis using a qualitative approach. Qualitative research methods are research methods based on the philosophy of positivism, used to research natural object conditions, (as opposed to experiments) where the researcher is the key instrument, data source sampling is carried out systematically.purposive and Snowball, Collection techniques with tri - angulation(combined), analysis and inductive or qualitative nature and the results of qualitative research emphasize meaning rather than generalization. The data collection technique is by conducting direct observations and interviews with sources that are used as objects and loci of research, namely the West Bandung Regency Social Service and the Joint Business Group (Kube) Amar Patria Unit 06 in Kerta Jaya Village, Padalarang District, West Bandung Regency, as well as documentation. from the results of observations, interviews and documentation are then arranged in narrative form and then an analysis is carried out on the materials obtained from the results of observations, interviews and documentation. The implementation of the Joint Business Group Program (KUBE) cannot be said to be optimal, there are still factors that inhibit the implementation of the policy, including, Socialization has not been carried out simultaneously and is only carried out at the beginning without following up on whether the socialization can be understood and understood by the group and KUBE members. And Assistance in marketing production results has not been running, and supporting infrastructure for the program is still felt to be minimal, many of the group members have difficulty in implementing the program.